PENANGGULANGAN KEKERASAN SEKSUAL TERHADAP ANAK DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Isti Inayati Ngaenah; Lutfan Muntaqo; Rohatun Nihayah (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2021)
The focus of this study is based on the author's anxiety about sexual violence against children which often occurs recently. This is very contrary to Islam and also humanity. The violence that recently occurred in Islamic boarding schools and also in educational institutions has made the word takdzim the mainstay of the perpetrator's weapon so that the victim will do things that are not wanted. PAI plays an important role in overcoming sexual violence, because educators must have a good attitude and humanize humans.